A alma do mundo nas canções de Elomar Figueira Mello - Rezeck, Fábio (2022)
This work was a qualitative study based on the perspective of Analytical Psychology, whose aim was to analyze the aspects of the Northeastern anima mundi present in the songs of Elomar Figueira Mello. Although much research relates music to Analytical Theory, there is a scarcity of works that involve the artistic making analyzed from the point of view of the world soul that the composer reveals. It was also found that the production of research involving the anima mundi could contribute to greater levels of knowledge about collectivity, as it is a symbolic and analytical approach, bringing important contributions to the understanding of the meanings implied in artistic constructions. The present research was based on the elomarian songbook, whose songs so richly portray the backlander in its tragedies and expressions of glory, bravery, and sensitivity, with Jungian theoretical foundations. The results revealed the existence of four main collective themes so named: the human trajectory (birth, development and death), the heroic spirit, the love (mis)encounters, and the backlander. Each of the themes contains collective representations specific to the experiences that are linked to them, such as the qualities, difficulties, fears, and ways of living of the backlander. The artist would thus be an interlocutor of his place and time in the face of representations of this collective soul, given the sensitivity he has when dealing with life's themes. The way he composes and the themes of his songs would be representations of this country's soul. The results also indicate that symbolic reading is an important resource for the understanding of artistic work and, more specifically, for the understanding of a world that remains one, despite so many transformations. We understand that the results found can serve as a basis for the continuity of studies related to the topic presented here